Cerebral Hemodynamics and Carotid Atherosclerosis in Patients With Subcortical Ischemic Vascular Dementia - Xiao-Jiao Liu (Frontiers Media S.A., 2021)
A growing body of evidence indicates that atherosclerosis is correlated with cerebral small vessel disease and contributes to cognitive decline. This study aimed to explore the characteristics and contributions of intracranial hemodynamics and carotid atherosclerosis to cognitive dysfunction in subjects with subcortical ischemic vascular dementia (SIVD). Notably, 44 patients with SIVD, 30 patients with Alzheimer’s disease (AD), and 30 healthy controls (HCs) were recruited from our longitudinal MRI study for AD and SIVD (ChiCTR1900027943). The cerebral mean flow velocity (MFV) and pulsatility index (PI) of both anterior and posterior circulations, artery plaque, and lumen diameter in carotid arteries were investigated using transcranial Doppler and carotid ultrasound, respectively. Their correlations with cognitive function were analyzed in patients with dementia. Decreased MFV and increased PI were found in patients with SIVD and AD. Patients with SIVD showed lower MFV and higher PI in the bilateral posterior cerebral arteries compared to patients with AD. Increases in lumen diameter, number of arteries with plaque, and total carotid plaque score were found in patients with SIVD. The Mini-Mental State Examination score was positively correlated with the MFV and negatively correlated with the PI of most major cerebral arteries, while it was negatively correlated with the lumen diameter of the common carotid artery, number of arteries with plaque, and total carotid plaque score in patients with dementia. There were also correlations between these parameters of some arteries and memory and executive function. Our results provide additional evidence suggesting that the pathological changes in macrovascular structure and function are correlated with cognitive impairment in dementia patients with SIVD and to a lesser extent AD.